ANNA AGUSTINA ENJOYING HER STUDIES AT USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 14 March 2016 – Universiti Sains Malaysia (USM) is well becoming a place that is close to the heart, especially for international students aiming to further their studies here.